A new species of Ologamasus (Acari: Ologamasidae) from Brazil - Silva, E. S.; de Moraes, G. J.; Krantz, G. W. (Zootaxa, 2007)
Ologamasus cananeiae sp. n. is described based on specimens representing all postembryonic stages, collected from litter in a forest area of southeastern Brazil. A key is provided to help in the separation of the seven species known worldwide.